External Fixation in Orthopedic Traumatology - Seligson, David; Mauffrey, Cyril; Roberts, Craig S.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
External fixation in Orthopedic traumatology is a textbook that focuses on the use of external fixation in the acute management of patients with serious orthopaedic injuries. The book highlights the indications for external fixation and provides an evidenced based guide to both the specialist orthopedic surgeon and the trainee. The manuscript is organised in 14 chapters covering the indications and surgical techniques for pelvis, lower limb and upper limb injuries, including detailed illustrations and clinical photographs that will enable the reader to rapidly visualise the structure of the construct and to plan the surgery accordingly. More general topics such as damage control orthopedics, the biomechanics of external fixation and medico-legal considerations surrounding the injured patients are also included to provide an overall picture of the Orthopedic trauma patient. The Combined experience of the editors and authors, their involvement in a number of external fixation system designs and their international reputation in the field contribute to making this textbook an essential tool that should be available to all orthopaedic surgeons dealing with injured patients.
Keywords: Orthopedics; Orthopedics; Conservative Orthopedics; Surgical Orthopedics